Social expectations or self-regulation?—study on tourists' comity behavior in taking photos - Dong Li; Dong Li; Zhaowen Duan; Xiaoliang Xu; Ying Chen; Xuyi Liu (Frontiers in Psychology)
IntroductionDuring travel, photos capture beautiful moments and serve as a visual narrative. However, achieving a satisfactory photo in crowded tourist scenes relies on tourists' mutual cooperation and courtesy. This study aims to explore tourists' courteous behavior in photo-taking through normative activation theory.MethodsStructural equation modeling.Results(1) Both social and individual norms positively affect courteous behavior, with individual norms having a greater impact; (2) Impression management motivation mediates the relationship between norms and courtesy; (3) Proactive personality moderates the link between individual norms and impression management but does not affect the link between social norms and impression management.DiscussionThis study expands the application of normative activation and impression management theories and offers practical insights for tourism management to encourage civilized behavior.